Boron neutron capture therapy for clear cell sarcoma. (December 2020) - Fujimoto, Takuya; Suzuki, Minoru; Sudo, Tamotsu; Fujita, Ikuo; Sakuma, Toshiko; Sakurai, Yoshinori; Hirose, Takanori; Morishita, Masayuki; Takata, Takushi; Tamari, Yuki; Tanaka, Hiroki; Andoh, Tooru; et al.
Abstract: Clear cell sarcoma of tendons and aponeuroses (CCS) is a rare, malignant tumor arising in lower extremities with no effective treatment other than wide surgical resection. Here described is a case of primary CCS in the peroneal tendon of the right foot of a 54-year-old woman enrolled to undergo BNCT. The tumor mass post-BNCT disappeared totally without damage to other normal tissue, demonstrating, for the first time, the potential efficacy of BNCT in complete local control of CCS. Highlights: First ever BNCT for clear cell sarcoma in tendon on right foot of 54-year-old woman. Two deferred courses of BNCT irradiation to two sides of foot eradicated the CCS. CCS cells expressing LAT1 uptake BPA selectively rendering them susceptible to BNCT.